Upaya Pemberdayaan Kelompok Wanita Tani dan Pencegahan Stunting melalui Pelatihan Permakultur di Desa Compong - Aksan, Muhammad; Febrianti, Devy; Latif, Adam; Said, Sunandar; Zain, Muhaidir M.; Azyarah, Faimah; Wardana, Harmadi; Armang, Arnis; Sari, Eka (Jurnal SOLMA, 2025)
Background: Compong Village is a village located in Pitu Riase Subdistrict, Sidenreng Rappang Regency, South Sulawesi. It is situated in a mountainous and hilly region with a significant amount of marginal land. This community service program aims to empower the residents of Compong Village through the introduction of permaculture on marginal land, specifically home gardens, targeting 28 members of the Melati Women Farmers Group (KWT) in Compong Village. The village has a high prevalence of stunting despite its substantial natural resource potential. Method: The implementation method involved intensive outreach and mentoring over three months (August-December 2024), consisting of several stages: situational and partner condition analysis, socialization, activity implementation, monitoring, evaluation, impact assessment, and expansion. Result: The Women Farmers Group successfully transformed barren and dry land into productive areas that not only met daily nutritional needs with nutritious food but also contributed to the family economy. Based on pre-test and post-test results from two key training and mentoring activities—focused on nutrition and stunting knowledge as well as organic permaculture outreach—the average knowledge of KWT members increased by more than 80%. Furthermore, they began generating sustainable income from permaculture food products cultivated through the program. Conclusion: It is hoped that in the future the permaculture garden (ProSegi) managed by the management of KWT Melati Dusun III can continue to be sustainable and empower the local community both socially, economically and in the community